Instrument development and validation for measuring competencies among polytechnic teachers in Malaysia - Arifin, Muhammad Aiman (2019)
One of the aims of human resource development (HRD) is to manage the career development of an employee, and to enhance his or her future performance in terms of knowledge, skills, and abilities or competencies. As for Polytechnic teachers, their competencies can affect the performance of their students and are an important component to support the practice of competency-based education in polytechnic institutions. Malaysia’s TVET education has recently faced the issue of a lack of competent teachers, in terms of on-the-job and personal competencies, including among polytechnic teachers. Through the competency-based approach, the objective of this study is to develop and validate an instrument for measuring competencies among polytechnic teachers in Malaysia, known as the Ma-PTCMI Instrument. This multiphase study comprised of competency identification and modelling, and the development of the competency measurement instrument, which was methodologically used to achieve the overall research objectives. To enhance the validity of this instrument, 11 experts from various institutional backgrounds have participated in this study. Subsequently, four interconnected competency constructs were proposed to develop a comprehensive framework for the Ma-PTCM model and the Ma-PTCMI instrument, namely teaching competencies, professional competencies, communication competencies, and personal competencies. The population of this study consisted of teachers from 28 polytechnics in Peninsular Malaysia. A total of 195 teachers took part in the overall instrument testing procedure. Then, 198 items were tested on 35 respondents in the first instrument testing (pilot study). During the second instrument testing, this instrument was refined, where 133 items were re-tested on 50 respondents. In the final instrument testing, 123 items were re-tested on 110 respondents and were identified as essential items to be included in the Ma-PTCMI instrument. The Winstep software (version 3.72.3) was used to analyse the collected data. Data analysis using the Rasch Measurement Model showed that the first version of the Ma-PTCMI instrument has an item reliability value of 0.91, with the item separation index of 3.21 and person reliability of 0.99, with separation index of 13.11. As for unidimensionality, the raw variance explained by measures was 60.0%. Unexplained variance in the 1st contrast of 8.8 % was obtained. The final version of the Ma-PTCMI instrument showed improved psychometric properties for item reliability of 0.97, with item separation index of 5.32 and person reliability of 0.99, with person separation index of 11.67. For unidimensionality, the raw variance explained by measures was 64.2%. Unexplained variance in the 1st contrast of 7.5% was obtained, which proved that it has improved from the first version. A total of 75 items were removed from the original instrument. The new self-assessment instrument consisted of 123 items and used the 5-point Likert scale. The Ma-PTCMI instrument fills a theoretical gap by extending the competency elements of a polytechnic teacher with a comprehensive set of required competencies from the Job and Personality perspectives. The Ma-PTCMI instrument may contribute towards providing related bodies with a framework of competency modelling and a self-assessment tool for assessing the competencies of polytechnic teachers. The outcome is expected to become input for future polytechnic teacher’s training and professional development intervention.